Iodine and ammonium persulfate mediated activation of DMSO: an approach to N-formylation of amides and synthesis of isatins. Issue 42 (13th October 2022) - Bhat, Showkat Ahmad; Bhat, Mohammad Yaqoob; Rather, Suhail A.; Gani, Ifshana; Bhat, Khursheed Ahmad; Ahmed, Qazi Naveed
Abstract : An efficient strategy towards N -formylation of amides and oxidation of indolines to isatins is described. Abstract : An efficient strategy towards N -formylation of amides and oxidation of indolines to isatins is described. This method employs readily available (NH4 )2 S2 O8, I2, and DMSO. The given method features operational simplicity, excellent functional group tolerance, broad substrate scope, and fast kinetics. Moreover, the method was applied to the synthesis of the natural product alatamide. Notably, DMSO plays three vital roles: a formyl group source, an oxidant, and a solvent.